Study of Low-Fat Ice Cream with The Substitution of Super Red Dragon (Hylocereus costaricensis) Fruit Peel - Hafids, Sahrial; Rahmi, Silvi Leila; Chairunisah, Annida Rani (Department of Technology of Agricultural product (THP) Jambi University, 2019)
Abstract— This research aimed to identify the effect of the substitution of super red dragon fruit peel (Hylocereus costaricensis) towards the physical and organoleptic characteristic of low-fat ice cream, todeterminethe best formulationof the Substitution of super red dragon fruit peel (Hylocereus costaricensis)intolow-fat ice creamand to determine whether the best formulation of low-fat ice cream with the substitution of super red dragon fruit peel (Hylocereus costaricensis)is as acceptable as commercial ice cream. This research was designed using a completely randomized design (CRD) with the substitutionof super red dragon fruit peel (0, 6, 8, 10, and 12% w/w) as the treatments. The parameters of overrun, melting time, viscosity, colour (L*, a* and b* values), and organoleptic evaluation including hedonic quality of colour and texture and overall acceptance were analyzed. The best treatment of organoleptic evaluation then was analyzed by paired comparison evaluation method with commercial ice cream. The result showed that the substitutionof super red dragon fruit peel was significantly different (P<0,01) on overrun, melting time, viscosity, colour (L*, a* and b* values), hedonic quality of colour and texture, and overall acceptance. The substitutionof 8% super red dragon fruit peel was found to be the best treatment based on organoleptic evaluation with overrun of 38,40%, melting time of 16,11 minutes, viscosity of 551,03 cP, colour; L* 63,80, a* 12,78, b* 19,25, hedonic quality of colour 3,10 (pink), texture 4,15 (smooth, non-snowy) and overall acceptance 4,45 (like moderately). The best formulation of low-fat ice cream with the substitution of 8% super red dragon fruit peel was not significantly different on the paired comparison evaluation with the score of 0,20 (Similar). Keywords— Ice cream; Low-fat; Peel; Super Red Dragon Fruit.